Contextual effects of varying amounts of language-mixed text on translation and comprehension by monolinguals and bilinguals - De La Garza, Bernardo (Kansas State University, 2008)
The present study examined the effects of discourse context information on English Monolinguals' and Spanish-English Bilinguals' ability to 1) translate Spanish and Finnish vocabulary words and 2) comprehend inferential and factual comprehension questions based on language-mixed prose. Language-mixed (i.e., codeswitched) prose varied in the number of foreign words presented in each sentence (i.e., 0, 1, 2, or 3 words per sentence). Results indicated that Monolinguals and Bilinguals' ability to translate Finnish words from pre-test to post-test increased due to their use of contextual information as an aid in translation. Furthermore, Monolinguals' translation accuracy increased from pre-test to post-test when tested on Spanish vocabulary words, but Bilinguals' translation difference scores did not increase from pre-test to post-test, due to their high prior knowledge of Spanish. Monolinguals and Bilinguals' comprehension accuracy was high throughout all conditions, even when tested on material conveyed by Finnish and Spanish words. Results from the study suggest that the use of language-mixed prose does not necessarily impair comprehension or translation ability for Monolinguals or Bilinguals, but in fact provides the context to help translate foreign vocabulary words and draw pragmatic inferences and factual information from text. The findings from this study are of importance in suggesting that, through the use of written contextual information, it is possible to learn basic foreign language vocabulary. Implications for foreign language learning, language-mixing as a mode of communication, and models of language acquisition and lexical access are discussed.
Keywords: Context; Language-Mixed; Translation; Comprehension; Monolinguals; Bilinguals; Psychology, Cognitive (0633)